Impact of diet adherence on weight and lipids among African American participants randomized to vegan or omnivorous diets - Gabrielle M. Turner‐McGrievy; Sara Wilcox; Edward A. Frongillo; E. Angela Murphy; Yesil Kim; Emily A. Hu; Nkechi Okpara; Shiba Bailey (Wiley, 2024)
Abstract Objective Prior research has found that plant‐based diets (PBDs) are rated as acceptable and have similar levels of adherence as compared to other therapeutic dietary approaches; however, previous studies were mostly among white populations. Plant‐based diets can produce clinically meaningful weight loss, but outcomes may vary by level of adherence. The goal of this study was to examine the differences in weight and lipids among participants in the Nutritious Eating with Soul study based on adherence to their diet assignment. Methods African American adults (n = 159; 79% female) with overweight or obesity (mean BMI 36.9 ± 6.9 kg/m2) were recruited to participate in a 24‐month intervention. Participants were randomized to a plant‐based vegan (n = 77) or a low‐fat omnivorous (n = 82) diet, both emphasizing soul food cuisine. Participants attended nutrition classes and had dietary intake/adherence (three 24‐h recalls; adherence score 1-5), body weight, lipids, and other secondary outcomes assessed at baseline, 6‐, 12‐, and 24 months. Participants who met at least half of the adherence criteria (≥2.5 out of 5) were categorized as adherents. Results At 24 months, adherent vegans lost 5% of their body weight, non‐adherent vegans lost −0.005%, adherent omnivores lost −0.03%, and non‐adherent omnivores lost −0.02%. Adherent vegans lost more weight (kg) than all other participants at both 6‐ (−3.32 ± 0.92 (−5.14, −1.49), p < 0.001) and 24 months (−3.27 ± 1.49 (−6.23, −0.31), p = 0.03). Adherent vegans also lost more weight than less adherent vegans (−3.74 ± 1.05 (−5.82, −1.65)), adherent omnivores (−4.00 ± 1.27 (−6.51, −1.48)), and less adherent omnivores (−2.22 ± 0.98 (−4.15, −0.28)) at 6 months and lost more weight than less adherent vegans at 24 months (−4.96 ± 1.8 (−8.54, −1.37)) (all p < 0.05). Adherent vegans had greater improvements in cholesterol‐to‐HDL ratio at 24 months (−0.47 ± 0.22 (−0.92, −0.03), p = 0.04) and greater decreases in insulin (−4.57 ± 2.16 (−8.85, −0.29), p = 0.04) at 6 months than all other participants combined. Conclusions The study points to the benefit of the use of a PBD for reducing weight, lipids, and insulin in African American adults, but also highlights the importance of supporting adherence to the PBD. Clinical Trials.Gov ID Nutritious Eating With Soul (The NEW Soul Study); NCT03354377.